2013
DOI: 10.4209/aaqr.2012.08.0217
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and Surface-Bound Microbial Contamination in Two Intensive Care Units of a Medical Center in Central Taiwan

Abstract: Samples of airborne and surface-bound microbial contamination were taken in two intensive care units of a large-scale medical center. Microbial analyses included total bacterial and fungal loads, as well as the four bacterial species of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Acinetobacter baumannii. Among the 114 surface samples taken from seven designated surface locations of room and equipment for each patient, P. aeruginosa was the most frequently detected (19.3%) and most abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
4
28
3
1
Order By: Relevance
“…With regard to the relationships between indoor air pollution and SBS-related symptoms, our study is not in all respects in agreement with earlier findings found in office workers (Huang et al, 2013). One phenomenon that may have existed was lower indoor air humidity at higher air exchange rates.…”
Section: Discussionsupporting
confidence: 80%
“…With regard to the relationships between indoor air pollution and SBS-related symptoms, our study is not in all respects in agreement with earlier findings found in office workers (Huang et al, 2013). One phenomenon that may have existed was lower indoor air humidity at higher air exchange rates.…”
Section: Discussionsupporting
confidence: 80%
“…It was worth noting that the standard deviations of Room B, D, E and G were higher than the average values, which exhibited considerable variations of fungal levels in these four rooms. The total fungal concentration found in this study was higher than the results reported by Chuaybamroong et al [6] (67 CFU/m 3 ), Rocha et al [10] (9 CFU/m 3 ), and Huang et al [11] (12 CFU/m 3 and 59 CFU/m 3 in ICU I and ICU II, respectively, during sampling consistency study). However, the result was lower than the average reported by Fumagalli et al [12], who found a value between 250 and 300 CFU/m 3 during restrictive visiting periods.…”
Section: Airborne Bacterial and Fungal Concentrationscontrasting
confidence: 81%
“…However, none of the studies were conclusive about the role of air microflora in nosocomial infection in the Intensive Care Unit (ICUs), especially if it is multidrug resistant (MDR). So far, very few studies had been done in the ICU environment such as Ríos-Yuil et al [5] mentioned about the presence of various nosocomially significant fungus in the ICU of a general hospital and Huang et al [6] tried to find out the potential correlation between airborne and surface contamination in two ICUs of Taiwan, and whether patient infections were related to microbial contamination in the ICU. Based on the limited background knowledge about microbial contamination of the ICU environment and their contribution to nosocomial infection in the ICU, the main objectives of this study were microbiological characterization of the air samples in relation to the nosocomial infections in the different ICUs at different periods in our tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%